2005
DOI: 10.1029/160gm09
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the origin and stability of chemically distinct reservoirs deep in Earth's mantle

Abstract: Seismic tomography is providing mounting evidence for large scale compositional heterogeneity deep in Earth's mantle, and also the diverse geochemical and isotopic signatures observed in oceanic basalts suggest that the mantle is not chemically homogeneous. Isotopic studies on Archean rocks indicate that mantle inhomogeneity may have existed for most of the Earth's history. One important component may be recycled oceanic crust, residing at the base of the mantle. We investigate, by numerical modeling, if such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 96 publications
2
9
0
Order By: Relevance
“…At depth, upper mantle slabs can be dynamically supported by viscous stresses, which may explain a transition of earthquake focal mechanisms from down‐dip extension to compression in the mid‐upper mantle [ Isacks and Molnar , 1971; Alpert et al , 2010]. Locally, magnification of pull forces is possible due to compositional effects, for example, in regions where density increases due to extensive eclogite formation [ Cloos , 1993; van Thienen et al , 2005]. Because of the uncertain significance of the above mechanisms, we treat the slab pull fraction ( f sp ) as a free parameter in our models.…”
Section: Methodsmentioning
confidence: 99%
“…At depth, upper mantle slabs can be dynamically supported by viscous stresses, which may explain a transition of earthquake focal mechanisms from down‐dip extension to compression in the mid‐upper mantle [ Isacks and Molnar , 1971; Alpert et al , 2010]. Locally, magnification of pull forces is possible due to compositional effects, for example, in regions where density increases due to extensive eclogite formation [ Cloos , 1993; van Thienen et al , 2005]. Because of the uncertain significance of the above mechanisms, we treat the slab pull fraction ( f sp ) as a free parameter in our models.…”
Section: Methodsmentioning
confidence: 99%
“…An important point shown by van Thienen et al, (2005) is that any layering around 660 km induced by the post-spinel phase transition makes the layer more stable over long time periods, presumably because it reduces the temperature drop across the layer and the convective velocities.…”
Section: 1 the Balance Between Chemical And Thermal Buoyancymentioning
confidence: 99%
“…Several mechanisms have been proposed for the early partial differentiation of the Earth's mantle, including fractional crystallization of a regular magma ocean (Solomatov and Stevenson 1993;Solomatov 2007), crystallization of a basal magma ocean (Labrosse et al 2007), which also explains the ultra-low seismic velocity zones (ULVZ) observed locally at the bottom of the mantle (Garnero and Helmberger 1995;Williams and Garnero 1996), 'upside-down' differentiation (Lee et al 2010), which consists of the formation, crystallization, and sinking of dense liquids in the upper mantle during the Earth's first billion year, and the recycling of a primitive crust (Tolstikhin et al 2006), which is supported by geochemical data (Boyet and Carlson 2006;Caro et al 2003Caro et al , 2004 and numerical models of convection (van Thienen et al 2004(van Thienen et al , 2005. Alternatively, models of mantle composition based on E-chondrite predict that the composition in main oxides of the lower mantle is different from that of the upper mantle (Javoy et al 2010).…”
Section: Early Differentiated Materials Versus Recycled Morbmentioning
confidence: 97%